A novel normalization for amide proton transfer CEST MRI to correct for fat signal-induced artifacts: application to human breast cancer imaging - Zimmermann, Ferdinand; Korzowski, Andreas; Breitling, Johannes; Meißner, Jan-Eric; Schünke, Patrick; Loi, Lisa; Zaiss, Moritz; Bickelhaupt, Sebastian; Schott, Sarah; Schlemmer, Heinz-Peter; Paech, Daniel; Ladd, Mark E.; et al. (Magnetic resonance in medicine, 2020)
Purpose The application of amide proton transfer (APT) CEST MRI for diagnosis of breast cancer is of emerging interest. However, APT imaging in the human breast is affected by the ubiquitous fat signal preventing a straightforward application of existing acquisition protocols. Although the spectral region of the APT signal does not coincide with fat resonances, the fat signal leads to an incorrect normalization of the Z-spectrum, and therefore to distorted APT effects. In this study, we propose a novel normalization for APT-CEST MRI that corrects for fat signal-induced artifacts in the postprocessing without the need for application of fat saturation schemes or water-fat separation approaches. Methods The novel normalization uses the residual signal at the spectral position of the direct water saturation to estimate the fat contribution. A comprehensive theoretical description of the normalization for an arbitrary phase relation of the water and fat signal is provided. Functionality and applicability of the proposed normalization was demonstrated by in vitro and in vivo experiments. Results In vitro, an underestimation of the conventional APT contrast of approximately −1.2% per 1% fat fraction was observed. The novel normalization yielded an APT contrast independent of the fat contribution, which was also independent of the water-fat phase relation. This allowed APT imaging in patients with mamma carcinoma corrected for fat signal contribution, field inhomogeneities, spillover dilution, and water relaxation effects. Conclusion The proposed normalization increases the specificity of APT imaging in tissues with varying fat content and represents a time-efficient and specific absorption rate-efficient alternative to fat saturation and water-fat separation approaches.
First published: 18 September 2019
Gesehen am 23.06.2020